Social judgement of L2 accented speech stereotyping and its influential factors - Kang, Okim; Yaw, Katherine (Journal of multilingual and multicultural development, 2024)
If extraneous information leads listeners to biased judgements, then their speech perceptions are likely to manifest distortion in that direction. This phenomenon is known as reverse linguistic stereotyping (RLS), which has been confirmed by 25 years of empirical study. Recent research on effects of listener background on ratings of speaker pronunciation and social judgments are likewise consistent with the concept of reverse linguistic stereotyping. In particular, one way of operationalising listener aberration is measuring a function of listener backgrounds and proclivity toward RLS along with a dimension of speaker social attractiveness, superiority, and dynamism. The current study examined to what extent listeners' background characteristics and RLS propensity factors affect their social judgements of second language (L2) accented speech. The background factors included learners' accent exposure, study abroad experience, the degree of foreign language study experience, and three RLS dimensions. Results suggest that listeners who hold negatively stereotyped expectations about LX accents tend to find accented speech less superior and less socially attractive. Findings offer implications to language education and various workforce-related communication in global contexts.